The Easy-to-Hard Effect in Human (Homo sapiens) and Rat (Rattus norvegicus) Auditory Identification - Liu, Estella H. (2008)
Training exercises can improve perceptual sensitivities. We examined whether progressively training humans and rats to perform a difficult auditory identification task led to larger improvements than extensive training with highly similar sounds (the easy-to-hard effect). Practice improved humans’ ability to distinguish sounds regardless of the training regimen. However, progressively trained participants were more accurate and showed more generalization, despite significantly less training with the stimuli that were the most difficult to distinguish. Rats showed less capacity to improve with practice, but still benefited from progressive training. These findings indicate that transitioning from an easier to a more difficult task during training can facilitate, and in some cases may be essential for, auditory perceptual learning. The results are not predicted by an explanation that assumes interaction of generalized excitation and inhibition, but are consistent with a hierarchical account of perceptual learning in which the representational precision required to distinguish stimuli determines the mechanisms engaged during learning.